Neutrophils: a subgroup of neglected immune cells in ALS - Cao, Wen; Fan, Dongsheng (Frontiers in Immunology, 2023)
Amyotrophic lateral sclerosis (ALS) is a chronic, progressive neurodegenerative disease characterized by the loss of motor neurons. Dysregulated peripheral immunity has been identified as a hallmark of ALS. Neutrophils, as the front-line responders of innate immunity, contribute to host defense through pathogen clearance. However, they can concurrently play a detrimental role in chronic inflammation. With the unveiling of novel functions of neutrophils in neurodegenerative diseases, it becomes essential to review our current understanding of neutrophils and to recognize the gap in our knowledge about their role in ALS. Thus, a detailed comprehension of the biological processes underlying neutrophil-induced pathogenesis in ALS may assist in identifying potential cell-based therapeutic strategies to delay disease progression.